If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x+5.6)=10x+20
We move all terms to the left:
6(x+5.6)-(10x+20)=0
We multiply parentheses
6x-(10x+20)+33.6=0
We get rid of parentheses
6x-10x-20+33.6=0
We add all the numbers together, and all the variables
-4x+13.6=0
We move all terms containing x to the left, all other terms to the right
-4x=-13.6
x=-13.6/-4
x=3+1/2.5
| 7x^2-35x+14=0 | | 2/5=m/70= | | 45=-x/8+51 | | -17-(18)=x/2 | | 3x^2-10x-82=0 | | 2r^2=40-11r | | x/7+19=4 | | x(x+8)=(8)(6) | | 100-3x=40 | | -5x-98=-10x+37 | | (8-3i)(2+5i)=0 | | 7x^+5x=6 | | 10-5x=-14-6x | | 5v+25=1/(2v+10) | | 3x1=4 | | 2(y/4-15/4)+y=9 | | h-8=-2 | | x^+6x+1=0 | | B=25+a | | y^=2y+24 | | 98+27+(10x+5)=180 | | (14x2+6x)=(55+13x2) | | (2x^2+7x-12)-(x^2-16)=0 | | 18+x=-4x-42 | | (9x)(9x)(9x)-9x=0 | | C=12+-1b | | 5^2+6^2=x^2 | | 4x^2-200x+625=0 | | 5^2+62^2=x^ | | 150000000=300000t | | (x-9)^=36 | | (2x^2+7-12)-(x^2-16)=0 |